Model Perjanjian Perkawinan Pasca Putusan MK No. 69/PUU-XII/2015 Perspektif Maqaṣhid al-Shari’ah Imam al-Shatibi - Muhamad Sifak; Rayno Dwi Adityo (MLIJo: Journal of Law and Islamic Thought, 2026)
This study examines the validity of the expansion of marital agreements following Constitutional Court Decision No. 69/PUU-XIII/2015, which allows such agreements to be made during the course of a marriage, unlike the previous provision under Article 29 of Law No. 1 of 1974 on marriage, which only permitted them to be made before or at the time of marriage. This type research used a normative legal method with a conceptual approach, utilizing secondary data consisting of primary legal materials, secondary, and tertiary legal materials obtained through library research and analyzed using a prescriptive approach and interpretative method. The result indicate that the expansion is legally valid as long as it fulfills the requirements of a valid agreement and does not conflict with applicable laws. From the perspective of Imam Al-Shatibi’s Maqaṣid Al-Shari’ah, this policy is consistent with the objectives of protecting property (hifz al-mal) and preservation of progeny (hifz al-nasl). Regarding the object of the agreement, its permissibility falls into the hajiyat (complementary) category, moving towards the dharuriyat (essential) in preserving those two objectives. Therefore, marital agreements can serve as a legal instrument for promoting justice, welfare, and harmony within the family.